Determining the students’ Motivation through Social Media Usage: in Abu Dhabi Schools United Arab Emirates - Hammadi, Mohamed Khalil Al; Noor, Mohd Asri Bin Mohd (European Journal of Multidisciplinary Studies, 2023)
This research aims to explore the trends in student motivation as determined by social media usage. For addressing this objective, literature support has been provided in a reasonable manner. Furthermore, questionnaire was developed through various items from existing literature for both social media usage and collaborative learning as measured through Five points likert scale. Meanwhile, data has been collected with the help of different techniques. A valid sample response of 403 respondents from different grades ranging from 9th to 12th has been collected from different schools as situated in Abu Dhabi, UAE. The study findings have been covered through descriptive statistics and both measurement model and structural model. The results through measurement model confirm the existence of reliability and validity of the construct, whereas the findings through structural model confirms the significant impact of social media usage on core dimensions of motivation. More specifically, it is found that there is a significant impact of social media usage on psychological needs, safety needs, esteem needs, belongingness and love, and self-actualization, respectively.  The study findings have provided some meaningful discussion for various policymakers specifically in the education sector. Finally, there are some limitations through which future directions are also determined.
Keywords: social media, student’s motivation, two step approach, UAE.